Successful Treatment of Hepatitis C in Renal Transplant Recipients With Direct‐Acting Antiviral Agents. Issue 5 (5th February 2016) - Sawinski, D.; Kaur, N.; Ajeti, A.; Trofe‐Clark, J.; Lim, M.; Bleicher, M.; Goral, S.; Forde, K. A.; Bloom, R. D.
Abstract : The direct‐acting antivirals (DAAs) constitute an emerging group of small molecule inhibitors that effectively treat hepatitis C virus (HCV) infection, a common comorbidity in end‐stage renal disease patients. To date, there are no data to guide use of these agents in kidney transplant patients. The authors collected data from 20 consecutive kidney recipients treated with interferon‐free treatment regimens for HCV at their center: 88% were infected with genotype 1; 50% had biopsy‐proved advanced hepatic fibrosis on their most recent liver biopsy preceding treatment (Metavir stage 3 fibrosis [F3] or F4); and 60% had failed treatment pretransplantation with interferon‐based therapy. DAA treatment was initiated a median of 888 days after renal transplantation. All patients cleared the virus while on therapy, and 100% have achieved a sustained virologic response at 12 weeks after completion of DAA therapy. The most commonly used regimen was sofosbuvir 400 mg daily in combination with simeprevir 150 mg daily. However, four different treatment approaches were used, with comparable results. The DAAs were well tolerated, and less than half of patients required calcineurin inhibitor dose adjustment during treatment. Eradication of HCV infection with DAAs is feasible after kidney transplantation with few treatment‐related side effects. Abstract : The authors describe 20 renal transplant recipients successfully treated posttransplant for hepatitis C with directacting antivirals. See also the article from Kamar et al onpage 1474 and the editorial from Saxena and Terrault onpage 1345 .